Development and Validation of Novel and Highly Sensitive Stability-Indicating Reverse Phase UPLC Method for Quantification of Dabrafenib and its ten Degradation Products - Grover, Parul; Bhardwaj, Monika; Mehta, Lovekesh; Naved, Tanveer; Handa, Vandana (Indian Journal of Pharmaceutical Education and Research, 2022)
Objectives: Dabrafenib is used as an active pharmaceutical ingredient acts as an inhibitor of the associated enzyme B-Raf, which plays a role in the regulation of cell growth. In the current study, we focused on developing a robust, highly sensitive and stabilityindicating RP-UPLC method for estimation of DBR and its degradation products for the very first time. A stress study has been performed to demonstrate the stability-indicating capability of the method. Materials and Methods: Chromatographic separation was achieved using advanced UPLC technology with high resolution on Acquity BEH C-18 (100 mm × 2.1 mm, 1.8 μm) column using a mobile phase composed of orthophosphoric acid and methanol with very less consumption of solvents results in an eco-friendly method. Analysis was performed at 225 nm detector wavelength with 5 µL of injection volume and 0.3 mL min-1 of flow rate. Results: Forced degradation study was performed under hydrolytic (acid, alkali and neutral), oxidative, photolytic and thermal degradation as per ICH Q1 (R2) guidelines. The optimized method was observed to be linear in the concentration range of 12.5 to 125ng mL-1 with R2 value of 1.0000. Conclusion: This is the first very sensitive stability-indicating UPLC method capable of separating dabrafenib and its ten degradation products at the nanogram (ng) level. The method was validated as stated by ICH guidelines.
Keywords: Dabrafenib; RP-UPLC; Validation; Stability-indicating; Forced degradation